Rancang Bangun Alat Praktek Simulasi Monotoring Keseimbangan Beban Listrik 3 Fasa Berbasis Iot - Pongoh, Deitje; Budiman, Marson (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The 3 phase system was developed because it has the advantage that the transmitted power can be greater than a 1 phase system with the same conductor size and electric current. This 3-phase electricity monitoring is carried out to determine the condition of the 3-phase electric current leading to the load whether it is balanced or not. The purpose of making this tool is to design a balance load monitoring tool via a smartphone remotely. Internet of Things (IoT) is a concept that aims to expand the benefits of continuously connected internet connectivity. PZEM-004T is a hardware that functions to measure parameters of voltage, current, active power, and power consumption (wh). NodeMCU is an open source IoT platform and an electronic board based on the esp8266 chip with the ability to run microcontroller functions and also an internet connection. The method used in this research is the design, manufacture of tools and testing. In software testing aims to assess the functions of the application running well and to test the relationship between hardware and software as a program. The test steps include testing from NodeMCU 8266 to the PZEM 004T sensor where this sensor is a current, voltage and power measuring sensor. This test uses the Internet of Things for monitoring from the web. The results of the study are a monitoring tool where the measured load in the R S T phase can be seen from the LCD screen and monitored remotely via a smartphone